Empowering wastewater treatment with step scheme heterojunction ternary nanocomposites for photocatalytic degradation of nitrophenol - Zhu Liu; Mah Roosh; Ming Lu; Aqsa Arshad; Wenqi Xian; Yuqiu Shen; Guocong Liu; Ali Bahadur; Shahid Iqbal; Sajid Mahmood; Khalid M. Alotaibi (Scientific Reports)
Abstract The ongoing challenge of water pollution necessitates innovative approaches to remove organic contaminants from wastewater. In this work, new two-dimensional S-scheme heterojunction photocatalysts Bi2O3/CdS and MoS2/Bi2O3/CdS that are intended for the effective photocatalytic destruction of 4-nitrophenol, a dangerous organic pollutant, are synthesized and characterized. Utilizing a solvothermal method, successfully generated these ternary nanocomposites, which were characterized through various techniques including X-ray diffraction (XRD), scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS), high resolution transmission electronmicroscopy (HRTEM), Brunauer-Emmett-Telle (BET) and diffuse reflectance spectroscopy (DRS). Our results demonstrated that the Bi2O3/CdS heterojunction achieved an 86% degradation rate of 4-nitrophenol, while the MoS2/Bi2O3/CdS composite exhibited exceptional photocatalytic performance, achieving nearly complete degradation (99%) within 120 min under visible light irradiation. Most importantly the improved photocatalytic activity of MoS2/Bi2O3/CdS heterojunction originated from the release of internal electric field in S-scheme heterojunction. This enhanced activity is attributable to the synergistic effects of the heterojunctions that facilitate more effective charge separation and generation with more OP and RP confirmed the composite synthesis using S-scheme. The S-scheme is further confirmed by XPS, DRS, XPS-VB and photocurrent response. These findings highlight the promising application of these advanced photocatalysts in real-world wastewater treatment processes, offering a sustainable solution to combat water pollution.